The myth of capitalism: monopolies and the death of competition - Tepper, Jonathan (Chichester, 2019)
"The Myth of Capitalism tells the story of how America has gone from an open, competitive marketplace to an economy where a few very powerful companies dominate key industries that affect our daily lives. Digital monopolies like Google, Facebook and Amazon act as gatekeepers to the digital world. Amazon is capturing almost all online shopping dollars. We have the illusion of choice, but for most critical decisions, we have only one or two companies, when it comes to high speed Internet, health insurance, medical care, mortgage title insurance, social networks, Internet searches, or even consumer goods like toothpaste. Every day, the average American transfers a little of their pay check to monopolists and oligopolists. The solution is vigorous anti-trust enforcement to return America to a period where competition created higher economic growth, more jobs, higher wages and a level playing field for all. The Myth of Capitalism is the story of industrial concentration, but it matters to everyone, because the stakes could not be higher. It tackles the big questions of: why is the US becoming a more unequal society, why is economic growth anemic despite trillions of dollars of federal debt and money printing, why the number of start-ups has declined, and why are workers losing out."